Altered Hemodynamics Associated with Pathogenesis of the Vertebral Artery Dissecting Aneurysms - Akira Kurata; Sachio Suzuki; Kazuhisa Iwamoto; Kuniaki Nakahara; Katsutoshi Abe; Madoka Inukai; June Niki; Makoto Sasaki; Kiyotaka Fujii; Shingo Konno; Shinichi Kan; Kazuaki Fukasaku (Stroke Research and Treatment)
The etiology of the vertebral dissecting aneurysms is largely unknown, and they frequently occurs in relatively healthy young men. Objectives and Methods. A series of 57 consecutive cases defined by angiography were evaluated with regard to deviation in the course of the affected and contralateral vertebral arteries. Division was into 3 types: Type I without any deviation, Type II with mild-to-moderate deviation but not over the midline; and Type III with marked deviation over to the contralateral side beyond the midline. Results. The most frequent type of VA running was Type III for the affected and Type I nonaffected side, with this being found in all 17 patients except one. All of the Type III dissections occurred just proximal to a tortuous portion, while in cases with Type-I- and Type-II-affected sides, the majority (33 of 39) occurred near the union of the vertebral artery. In 10 of 57, a non-dominant side was affected, all except one being of Type I or II. With 12 recent patients assessed angiographically in detail for hemodynamics, eleven patients showed contrast material retrograde inflowing into the pseudolumen from the distal portion of the dissection site. Turbulent blood flow was recognized in all of these patients with retrograde inflow. Conclusions. Turbulent blood flow is one etiology of vertebral artery dissection aneurysms, with the sites in the majority of the cases being just proximal to a tortuous portion or union of vessels. In cases with dissection proximal to the tortuous course of the vertebral artery, retrograde inflow will occur more frequently than antegrade, which should be taken into account in designing therapeutic strategies.